Пьесы - Островский Александр Николаевич (Библиотека школьника, 2006)
8-11кл Экземпляры: ф-4 (20200206) / Инвентарный номер: 54841 / Цена: 150.00 / Сис.шифр: Р1 / Авт.знак: О-77 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1